The psychosocial purpose of driving and its relationship with the risky driving behaviour of young novice drivers. (August 2015) - Scott-Parker, B.; King, M.J.; Watson, B.
Highlights: Psychosocial driving purpose (independence, freedom, etc.) important for young driver. Developed the brief PsychoSocial Purpose Driving Scale (PSPDS). PSPDS found to be reliable and valid. Psychosocial purpose explained 34% of males' self-reported risky driving behaviour. Abstract: Background: The overrepresentation of young drivers in road crashes, injuries and fatalities around the world has resulted in a breadth of injury prevention efforts including education, enforcement, engineering, and exposure control. Despite multifaceted intervention, the young driver problem remains a challenge for injury prevention researchers, practitioners and policy-makers. The intractable nature of young driver crash risks suggests that a deeper understanding of their car use – that is, the purpose of their driving – is required to inform the design of more effective young driver countermeasures. Aims: This research examined the driving purpose reported by young drivers, including the relationship with self-reported risky driving behaviours including offences. Methods: Young drivers with a Learner or Provisional licence participated in three online surveys ( N 1 = 656, 17–20 years; N 2 = 1051, 17–20 years; N 3 = 351, 17–21 years) as part of a larger state-wide project in Queensland, Australia. Results: A driving purpose scale was developed (the PsychoSocial Purpose Driving Scale, PSPDS), revealing that young drivers drove for psychosocial reasons such as for a sense of freedom and to feel independent. Drivers who reported the greatest psychosocial purpose for driving were more likely to be male and to report more risky driving behaviours such as speeding. Drivers who deliberately avoided on-road police presence and reported a prior driving-related offence had significantly greater PSPDS scores, and higher reporting of psychosocial driving purposes was found over time as drivers transitioned from the supervised Learner licence phase to the independent Provisional (intermediate) licence phase. Discussion and conclusions: The psychosocial needs met by driving suggest that effective intervention to prevent young driver injury requires further consideration of their driving purpose. Enforcement, education, and engineering efforts which consider the psychosocial purpose of the driving are likely to be more efficacious than those which presently do not. Road safety countermeasures could reduce the young driver's exposure to risk through such mechanisms as encouraging the use of public transport.